Some aspects of the growth of two wheat varieties under field conditions : a thesis ... for the degree of Master of Agricultural Science in Plant Science. - Gandar, Paul Weston (Massey University, 1970)
This study provides some basic information on the growth and development of two wheat varieties under field conditions. The varieties chosen, Raven, a standard commercial variety of Australian origin, and Pitic 62, a high-yielding Mexican semidwarf wheat, provided a contrast in grain to straw ratio which reflected the trend in wheat breeding towards varieties with an increased proportion of grain to total dry weight. In field trials in the Manawatu Pitic 62 had outyielded Raven and the difference had been attributed to increased tillering in the semidwarf variety (J. M. McEwan, pers. comm.). However critical information on the physiological processes underlying the superior yields of semidwarf wheats sucn as Pitic 62 under New Zealand conditions was lacking and there was little published work elsewhere. A preliminary attempt to rectify this deficiency by examining the growth of one semidwarf and one standard variety was made in this experiment. [From Introduction]
Keywords: Wheat varieties